2020
DOI: 10.1155/2020/7606938
|View full text |Cite
|
Sign up to set email alerts
|

DHA Supplementation Attenuates MI-Induced LV Matrix Remodeling and Dysfunction in Mice

Abstract: Objective. Myocardial ischemia and reperfusion (I/R) injury is associated with oxidative stress and inflammation, leading to scar development and malfunction. The marine omega-3 fatty acids (ω-3 FA), eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA) are mediating cardioprotection and improving clinical outcomes in patients with heart disease. Therefore, we tested the hypothesis that docosahexaenoic acid (DHA) supplementation prior to LAD occlusion-induced myocardial injury (MI) confers cardioprotecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 70 publications
1
11
0
Order By: Relevance
“…It may, therefore, be useful to consider related literature as a context for our findings regarding omega-3 effects on IL-10. The most relevant finding is that C57BL/6N mice receiving a diet rich in DHA (Linoleic 2.9 g/kg, Linolenic 0.43 g/kg, and DHA 0.26 g/kg) for 7 days before myocardial I/R displayed decreased IL-10 mRNA expression 72 h after reperfusion, similar to our findings at 2 days post-CPIP ( Habicht et al, 2020 ). Furthermore, DHA supplementation also reduced TNF and IL-1β expression at 72 h post-I/R injury and was associated with a strong increase in the phenotype of alternatively activated Ly6C + macrophages at 14 days post-injury ( Habicht et al, 2020 ).…”
Section: Discussionsupporting
confidence: 87%
“…It may, therefore, be useful to consider related literature as a context for our findings regarding omega-3 effects on IL-10. The most relevant finding is that C57BL/6N mice receiving a diet rich in DHA (Linoleic 2.9 g/kg, Linolenic 0.43 g/kg, and DHA 0.26 g/kg) for 7 days before myocardial I/R displayed decreased IL-10 mRNA expression 72 h after reperfusion, similar to our findings at 2 days post-CPIP ( Habicht et al, 2020 ). Furthermore, DHA supplementation also reduced TNF and IL-1β expression at 72 h post-I/R injury and was associated with a strong increase in the phenotype of alternatively activated Ly6C + macrophages at 14 days post-injury ( Habicht et al, 2020 ).…”
Section: Discussionsupporting
confidence: 87%
“…ROS generation and inflammation also act as preferential agents in response to myocardial I/R insult despite apoptotic cascades 5 , 33 . To further reveal KDM3A’s participation in modulating ROS formation, in situ DHE staining together with the activity of antioxidative SOD and the content of the oxidative marker MDA were determined essentially.…”
Section: Resultsmentioning
confidence: 99%
“…Once oxidative stress disrupts the balance between antioxidant defence and ROS in favour of the latter, it constitutes a crucial aetiological component of MIRI 10 . Excessive ROS elicits an imbalanced redox status, particularly as reflected by the inactivation of the antioxidant enzyme SOD and increased MDA levels 11 , 14 , 33 . Furthermore, inflammation has been proposed to aggravate MIRI 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-10 acts primarily with immunosuppressive functions on leukocytes, whereas other members of the family act preferentially on epithelial cells, where they control defense mechanisms against viral, bacterial, and fungal infections, protect tissue integrity, and promote repair and regeneration 32,33 . DHA supplementation promotes the reduction of IL-10 synthesis by conferring cardioprotection in a myocardial injury model 34 . A study with the essential oil of Polygonum minus identified BCP as one of its components and used it as a positive control in the cisplatin-induced hepatotoxicity model, demonstrating a reduction in the concentration of IL-10 and, therefore, hepatoprotection 35 www.nature.com/scientificreports/ the reduction in our study demonstrates protection against exacerbation of inflammation during the infectious process.…”
Section: Discussionmentioning
confidence: 99%